Enhanced performance of visible-light-induced Bi2MoO6–N-doped biochar for rhodamine B degradation and textile wastewater decontamination - Rajesh Chanda; Anik Karmokar; Md. Nahid Hassan; Toslim Jahid; Shoyeb Muhammad; Nirupam Aich; Biplob Kumar Biswas (Case Studies in Chemical and Environmental Engineering)
Organic dyes are a significant source of growing wastewater pollution. Biochar-supported visible-light photocatalysts are gaining attention due to their cost-effectiveness and green perspective. This study presents a novel N-doped-coconut-husk-derived biochar (NBC)-supported bismuth molybdate (BMO) as a photocatalyst. Urea, KOH were mixed with coconut-husk and pyrolyzed at 600–800 °C to prepare NBC. The ball-mill mixed BMO-NBC composites having 77 wt% BMO-23 wt% of 800 °C pyrolyzed NBC degraded 99.1 % of 10 mg/L RhB solution within 120 minutes. The photocatalyst was evaluated for on-site-collected textile-effluent remediation. The role of biochar functionalization, pyrolysis temperature, as well as composite composition, in its photocatalytic performance, are presented.